Kewenangan Komisi Pemilihan Umum dalam Menetapkan Pasangan Calon Presiden dan Wakil Presiden - M. Zainuddin MZ (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2015)
Abstract: The General Election Commission (KPU) is national, permanent, and independent general election organizers. General election, which is held to elect members DPR, DPRD, DPD, the president and vice president, is a means of implementing the rule of the people who carried out directly, generally, freely, confidentially, honestly and fairly in the Unitary State of the Republic of Indonesia based on Pancasila and Constitution of the Republic of Indonesia (UUD) 1945. Within the Islamic political jurisprudence’s perspective, the duties and authorities of the General Election Commission in selecting the candidate for president and vice president participants are not contrary to the principles or the Islamic teachings. They also more emphasize to consultation and transparency in justice in doing the job. Otherwise, KPU can also be equated with ahlul halli wal aqdi institution. This institutions has the authority to decide and accommodate the aspirations of the people and institutions that have duty to determine a leader. Keywords: Electoral commission, president, Islamic political jurisprudence.